2014
DOI: 10.3389/fnhum.2014.00215
|View full text |Cite
|
Sign up to set email alerts
|

Creativity—the unconscious foundations of the incubation period

Abstract: Creativity is one of the most important assets we have to navigate through the fast changing world of the 21st century. Anecdotal accounts of creative individuals suggest that oftentimes, creative discoveries result from a process whereby initial conscious thought is followed by a period during which one refrains from task-related conscious thought. For example, one may spend an embarrassing amount of time thinking about a problem when the solution suddenly pops into consciousness while taking a shower. Not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(65 citation statements)
references
References 91 publications
1
57
0
7
Order By: Relevance
“…Without the time specification, things tend not to occur. Ritter and Dijksterhuis (2014) pointed out how important the idea of incubation was as part of the creative process. This is a required time for the conscious thought to be diverted from the task at hand, a time of defocusing for ideas to percolate.…”
Section: Intentional Professional Developmentmentioning
confidence: 99%
“…Without the time specification, things tend not to occur. Ritter and Dijksterhuis (2014) pointed out how important the idea of incubation was as part of the creative process. This is a required time for the conscious thought to be diverted from the task at hand, a time of defocusing for ideas to percolate.…”
Section: Intentional Professional Developmentmentioning
confidence: 99%
“…Horng and Hu's (2008) creativity process study cited in this research is also based on the stages of creativity process suggested by Wallas (1926). Therefore, it is necessary to shortly explain these stages proposed by Wallas (1926) (Akat, Budak and Budak, 1994;Rawlinson, 1995;Sio and Rudowicz, 2007;Horng and Hu, 2008;Sio and Ormerod, 2009;Üstündağ, 2009;Ritter and Dijksterhuis, 2014;Truman, 2011):…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…After one has formulated a problem there may be an 'incubation' phase before a solution is found. During this 'incubation phase' (Hamard, 1954, pp.13-15;Sio & Ormerod, 2009;Ritter & Dijksterhuis, 2014), we are not conscious of trying to solve a problem. However, the fact that we can suddenly reach insight out of the blue has been taken as an indication of subconscious processing.…”
Section: Decoupled Processing: Subliminal Preconscious and Consciousmentioning
confidence: 99%